Prevalence and determinants of hypertension among Bhutanese monks in Tashi-Choe-Dzong, Thimphu, Bhutan - Tshering, Namgay (Chulalongkorn University, 2013)
Thesis (M.P.H.)--Chulalongkorn University, 2010